Suggested activities for an ecological study of a mangrove ecosystem - Castillo, Lota Corazon Talenting 1949- (1978)
This study developed and tried out activities utilizing a mangrove system. Preliminary to the development of the activities, the investigator conducted a thorough ecological study of the mangrove's biotic and abiotic components which covered a period from December 6-12, 1977 at Buaya, Mactan, Cebu.Transect method was used in this study. It was recommended that: (1) the activities be taken as a part of a resource unit in ecology; (2) before utilizing the mangrove swamp for fishpond culturing and other aquaculture projects, studies should be conducted; and (3) government agencies should dessiminate information regarding the importance of mangroves.